Effect of time of day and specialty on polyp detection rates in Australia. Issue 5 (8th January 2019) - Zorron Cheng Tao Pu, Leonardo; Lu, Kevin; Ovenden, Amanda; Rana, Khizar; Singh, Gurfarmaan; Krishnamurthi, Sudarshan; Edwards, Suzanne; Wilson, Bill; Nakamura, Masanao; Yamamura, Takeshi; Ruszkiewicz, Andrew; Hirooka, Yoshiki; et al.
Abstract: Background and Aim: Adenoma detection rate (ADR) is an important quality metric in colonoscopy. However, there is conflicting evidence around factors that influence ADR. This study aims to investigate the effect of time of day and endoscopist background on ADR and sessile serrated adenoma/polyp detection rate (SSA/P‐DR) for screening colonoscopies. Methods: Consecutive patients undergoing colonoscopy in 2016 were retrospectively evaluated. Primary outcome was the effect of time of day and endoscopist specialty on screening ADR. Secondary outcomes included evaluation of the same factors on SSA/P‐DR and other metrics and collinearity of ADR and SSA/P‐DR. Linear regression models were used for association between ADR, time of day, and endoscopist background. Bowel preparation, endoscopist, session, patient age, and gender were adjusted for. Linear regression model was also used for comparing ADR and SSA/P‐DR. Chi‐square was used for difference of proportions. Results: Two thousand six hundred fifty‐seven colonoscopies, of which 558 were screening colonoscopies, were performed. The adjusted mean ADR (screening) was 36.8% in the morning compared with 30.5% in the afternoon ( P  < 0.0001) and was 36.8% for gastroenterologists compared with 30.4% for surgeons ( P  < 0.0001). For every 1‐h delay in commencing the procedure, there was a reduction in mean ADR by 3.4%. Using a linear regression model, a statistically significant positive association was found between ADR and SSA/P‐DR ( P  < 0.0001). Conclusions: Morning and afternoon sessions and gastroenterologists and surgeons achieved the minimum standards recommended for ADR. Afternoon lists and surgeons were associated with a lower ADR compared with morning and gastroenterologists, respectively. Additionally, SSA/P‐DR showed collinearity with ADR.